Relationship Between Organizational Climate And Self-Concept With Effectiveness Of Interpersonal Communication - Aria Nur Farida Muslicha; Nurbianta Nurbianta; Sri Endang Herudiati (International Journal of Educational Management and Innovation, 2022)
The research was conducted to determine whether there is a significant relationship between Organizational Climate and Self-Concept with the effectiveness of interpersonal communication at the Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tanjung Redeb. This study was designed using a quantitative correlational approach through survey methods. The target population was all 45 educators and education staff at the Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tanjung Redeb. The number of research samples is 30 teaching staff. Samples were purposive random sampling. This study indicates a significant relationship between organizational climate (X1) and head interpersonal communication (Y) effectiveness with the percentage contribution of variable X1 to Y of 40%. Then there is a significant relationship between Self-Concept (X2) and the Effectiveness of Head Interpersonal Communication (Y) with a correlation coefficient of ry2 = 0.628. The results then show that there is a significant relationship between Organizational Climate (X1) and Self-Concept (X2) with the Effectiveness of Leader Interpersonal Communication (Y) with a correlation coefficient of ry12 = 0.707 and the coefficient of determination r2y12 = 0.262 significant at 0.05. It shows that 50% of the leaders' interpersonal communication is determined jointly by organizational climate and self-concept. The research finding indicated a good atmosphere related to the organizational climate provides comfort for each individual to build a positive self-concept, which is related to the effective interpersonal communication of institutional leaders. Where there was never found in the previous research, the combination of organizational climate and self-concept influences the effectiveness of Interpersonal communication simultaneously.